1988
DOI: 10.2190/yevw-6c44-ycye-cgeu
|View full text |Cite
|
Sign up to set email alerts
|

Corporatization and the Social Transformation of Doctoring

Abstract: Corporatization of health care is dramatically transforming the medical workplace and profoundly altering the everyday work of the doctor. In this article, the authors discuss recent changes in U.S. health care and their impact on doctoring, and outline the major theoretical explanations of the social transformation of medical work under advanced capitalism. The adequacy of the prevailing view of professionalism (Freidson's notion of professional dominance) is considered, and an alternative view, informed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(100 citation statements)
references
References 35 publications
0
92
0
8
Order By: Relevance
“…Barley, 1986;Mort et al, 2009;Oborn et al, 2011;Petrakaki et al, 2012). Finally, technology may at times create more agentic roles for patients giving them greater access to personal health information and more involvement in the process of their own care, for instance through electronic booking of appointments with doctors of their choice or access to records, further challenging healthcare professionals' power (Haug, 1988;Hasselbladh & Bejerot, 2007;McKinlay & Stoeckle, 1988;Mort et al, 2009). …”
Section: Changes In Healthcare Professional Work Afforded By Technologymentioning
confidence: 99%
“…Barley, 1986;Mort et al, 2009;Oborn et al, 2011;Petrakaki et al, 2012). Finally, technology may at times create more agentic roles for patients giving them greater access to personal health information and more involvement in the process of their own care, for instance through electronic booking of appointments with doctors of their choice or access to records, further challenging healthcare professionals' power (Haug, 1988;Hasselbladh & Bejerot, 2007;McKinlay & Stoeckle, 1988;Mort et al, 2009). …”
Section: Changes In Healthcare Professional Work Afforded By Technologymentioning
confidence: 99%
“…facilitative and non directive administration; disconnected, bottom up and incrementally expansionist bids from core professionals; a weak strategic core) (see Denis et al, 1991, for an empirically informed study of similar processes in an empirical study of strategic planning in Canadian hospitals). Freidson (1985Freidson ( , 2001) later revised his original professional dominance thesis to concede there was some movement away from it but such change was seen as less radical than by more radical 'deprofessionalisation' authors (McKinlay and Arches, 1985;McKinlay and Stoeckle, 1988). A preferred alternative scenario was one of 'professional restratification' whereby professional elites (especially two forms of managerial and knowledge based elites) separated themselves out from the professional rank and file (see also Waring 2014 for a more developed typology).…”
Section: Putting Public Management Scholarship Back Into the Npmmentioning
confidence: 99%
“…Much of this research argued that the medical profession's autonomy has been eroded from the 1960s-1970s, while it was characterised until then by a high level of self-regulation (Freidson 1970). Proletarianisation and corporatisation theories suggested that the expansion of capitalism involved a process of deskilling and routinisation of medical work, resulting from an increasing physicians' dependency on corporate organisations and administrative bureaucracy (McKinlay and Stoeckle 1988). Although such perspectives have been deemed exaggerated (Hafferty and Light 1995), they pointed out some of the significant changes that have transformed organisation of health care systems and the nature of medical work over the past decades.…”
Section: Malpractice Claims As a Challenge To Professional Dominancementioning
confidence: 99%